Pejibaye´s larger stems produced in the Vale do Ribeira are more productives - Salgado, Gabriel Henrique dos Santos Silva; Ferrari, Samuel; Enke, Dariane Beatriz Schoffen (Revista de Ciências Agroveterinárias, 2020)
The interest for pejibaye crops started to grow after the 70’s decade, due to the agronomic qualities, ecological, industrials and commercials. The São Paulo State is highlighted as one of the biggest pejibaye growers of the country, most concentrated at Vale do Ribeira. It was objectified with this work to evaluate characteristics of vegetative growth of plants as well as the ideal cutting time for stems in cultivation with different population densities, for the second year of cutting, aiming at the heart-of-palm yield of pejibaye. The experimental design was used in a 2x5 factorial, with treatments with five classes of cutting height (1,60 m, 1,90 m, 2,20 m, 2,50 m and 2,80 m) and two densities of plants (5,000 and 10,000 plants ha-1). The experiment was led on Campus Experimental de Registro UNESP’s farm. The analyzes were performed on march 16th and 17th of 2016 and September 01st e 19th of the same year. Stems of pejibaye at cutting height of 2,8 m and harvested in march obtained a larger number of leaves, a larger diameter of the stem in relation to the other heights and larger total amount of heart-of-palm produced. Stems with the same cutting height, but harvested in the month of September, provided greater production of minced hearts-of-palm, slice, thole and total amount of pejibaye heart-of-palm.